The role of the clinical and translational science awards program in improving the quality and efficiency of clinical research. - Rosenblum D; Alving B; Rosenblum, Daniel; Alving, Barbara (CHEST, 2011)
Recognizing the need to increase the efficiency and quality of translating basic discovery into treatment and prevention strategies for patients and the public, the National Institutes of Health (NIH) announced the Clinical and Translational Science Awards (CTSAs) in 2006. Academic health centers that competed successfully for these awards agreed to work as a consortium and in cooperation with the NIH to improve the translation process by training the next generation of investigators to work in interdisciplinary teams, developing public-private partnerships in the movement of basic discovery to preclinical and clinical studies and trials, improving clinical research management, and engaging with communities to ensure their involvement in shaping research questions and in implementing research results. The CTSAs have addressed the crucial need to improve the quality and efficiency of clinical research by (1) providing training for clinical investigators and for bench researchers to facilitate their participation in the clinical and translational research environment, (2) developing more systematic approaches to clinical research management, and (3) engaging communities as active participants in the design and conduct of clinical research studies and trials and as leaders in implementing health advances that are of high importance to them. We provide an overview of the CTSA activities with attention to these three areas, which are essential to developing efficient clinical research efforts and effective implementation of research results on a national level.